2000
DOI: 10.1139/cjfr-30-1-156
|View full text |Cite
|
Sign up to set email alerts
|

Predicting tree mortality from diameter growth: a comparison of maximum likelihood and Bayesian approaches

Abstract: Ecologists and foresters have long noted a link between tree growth rate and mortality, and recent work suggests that interspecific differences in low growth tolerance is a key force shaping forest structure. Little information is available, however, on the growth-mortality relationship for most species. We present three methods for estimating growth-mortality functions from readily obtainable field data. All use annual mortality rates and the recent growth rates of living and dead individuals. Annual mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Dashed vertical lines represent light variability due to uncertainty on parameter estimates. b Distribution of cells with less than 5% relative light when considering mean specific allometries (filled grey bars) is compared to the mean distribution of cells on the 500 simulations when including uncertainty in parameters (unfilled grey bars) and to the distribution of cells when including individual variability (unfilled black bars) ecological processes such as fecundity (Clark et al 2004(Clark et al , 2007 and mortality (Bigler and Bugmann 2003;Kobe and Coates 1997;Kunstler et al 2005;Wyckoff and Clark 2000), which drive community dynamics. As suggested by Parish et al (2008), the large intraspecific variability resulting in major overlap among species in structural characteristics should greatly reduce the rates or potential for competitive displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Dashed vertical lines represent light variability due to uncertainty on parameter estimates. b Distribution of cells with less than 5% relative light when considering mean specific allometries (filled grey bars) is compared to the mean distribution of cells on the 500 simulations when including uncertainty in parameters (unfilled grey bars) and to the distribution of cells when including individual variability (unfilled black bars) ecological processes such as fecundity (Clark et al 2004(Clark et al , 2007 and mortality (Bigler and Bugmann 2003;Kobe and Coates 1997;Kunstler et al 2005;Wyckoff and Clark 2000), which drive community dynamics. As suggested by Parish et al (2008), the large intraspecific variability resulting in major overlap among species in structural characteristics should greatly reduce the rates or potential for competitive displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, growth-mortality functions are based on the most recent five years of growth (Kobe et al 1995;Wyckoff and Clark 2000). However recent work has documented a relationship between longer-term growth characteristics and tree decline, including lifetime growth rates, long-term growth trends and abrupt changes in growth (Pedersen 1998;Cherubini et al 2002;Suarez et al 2004).…”
Section: Modeling Non-catastrophic Tree Mortalitymentioning
confidence: 99%
“…Several studies have shown that tree defoliation, mean radial growth and radial growth trends are, to some extent, inversely related (Buchman et al 1983;Kobe and Coates 1997;Wyckoff and Clark 2000;van Mantgem et al 2003). However, the potential interacting effects of long-term growth patterns and short-term growth sensitivity to climate on decline probability, and their use as surrogates for evaluating the vulnerability of tree species to climate change, have received less attention (Pedersen 1998b;Das et al 2007).…”
Section: Introductionmentioning
confidence: 99%